OSIRIS‐REx Visible and Near‐Infrared Observations of the Moon. Issue 12 (19th June 2019) - Simon, A. A.; Donaldson Hanna, K. L.; Drouet d'Aubigny, C. Y.; Poggiali, G.; Emery, J. P.; Brucato, J.; Cosentino, R. G.; Reuter, D. C.; Golish, D. R.; DellaGiustina, D. N.; Lunsford, A.; Gorius, N.; et al.
Abstract: The Origins, Spectral Interpretation, Resource Identification, and Security‐Regolith Explorer (OSIRIS‐REx) mission observed the Moon during the spacecraft's Earth gravity assist in 2017. From the spacecraft view, the lunar phase was 42°, and the in‐view hemisphere was dominated by anorthositic highlands terrain. Lunar spectra obtained by the OSIRIS‐REx Visible and InfraRed Spectrometer show evidence of several candidate absorption features. We observe the 2.8‐μm hydration band, confirming the spectral results from other missions, but detected in full‐disk spectra. We also tentatively identify weak spectral features near 0.9 and 1.3 μm, consistent with lunar regolith containing a mixture of plagioclase and orthopyroxene minerals, as expected for highlands terrain. Plain Language Summary: The Origins, Spectral Interpretation, Resource Identification, and Security‐Regolith Explorer mission obtained observations of Earth and the Moon during a 2017 gravity assist maneuver. The Origins, Spectral Interpretation, Resource Identification, and Security‐Regolith Explorer Visible and InfraRed Spectrometer acquired several spectra that covered the fully illuminated portion of the Moon. These spectra show absorption features consistent with the mineral mixtures expected in the lunar Highlands terrains. Near‐simultaneous images show that the side of the Moon that was visible is dominated by this type of terrain. In addition, an infrared absorption, consistent with water‐bearing minerals, is also observed, confirming the spectral identifications made by previous missions that have observed the Moon. Key Points: The OSIRIS‐REx mission obtained observations of Earth and the Moon during a 2017 gravity assist maneuver Visible and near‐infrared spectra of the Moon show features consistent with plagioclase‐dominated mixtures expected in highlands terrain The 2.8‐μm hydration band is observed in full‐disk spectra, confirming previous spacecraft observations